Pand[e]monium - Sayers, James, 1748-1823 (Cornell, Thomas, 1784)
Scholarly notes may be added at a later date.
"All these and more came flocking ... " Miltons Paradise lost
1 print : b&w
Keywords: Caricatures; Cartoons; Milton, John, 1608-1674 -- Paradise lost.; Fox, Charles James, 1749-1806; Burke, Edmund, 1729-1797